"An aliphatic essential amino acid influences the expression of host defense peptides in colonic epithelial cells: in vitro findings and potential clinical implications in Crohn's disease" - Osei-Boadi, Kate (Kansas State University, 2014)
Background and Objective: Crohn’s disease (CD) patients express low levels of host defense peptides (HDPs) especially β-defensins, which may compromise intestinal barrier function. Antibiotic treatment for bacterial infections in CD is limited and rarely curative, making it necessary to find alternative therapeutic approaches. We therefore investigated to what extent an essential amino acid; L-isoleucine (L-ILE) might induce the expression of human β-defensins (HBDs) in colonic epithelial cells as an alternative approach to help patients with CD. Antimicrobial activity of HBD2 was also assessed against four bacterial isolates which can cause secondary infections in CD. Methods: HTB-37 Caco-2 cells were stimulated with L-ILE at a concentration of 0 - 500µg/ml for 6 hours. Total RNA was extracted using RNeasy Micro Kit (QIAGEN). Reverse transcription was carried out with Superscript ®III First-Strand Synthesis System. The cDNA was amplified using specific primers for HBD1-3. Antimicrobial activity of HBD2 was determined using the broth dilution assay. Results: HBD1 was constitutively expressed under all conditions. HBD2 was expressed in HTB-37 cells after stimulation with L-ILE. Below 25µg/ml L- ILE stimulation, no expression of HBD2 was observed. HBD2 exhibited antimicrobial activity against bacterial isolates tested, with a MIC of 32, 64 and 128 µg/ml for both strains of E. coli, S. aureus and P. aeruginosa respectively. Conclusions: Our results indicate that L-ILE stimulation of HTB-37 Caco-2 cells can induce HBD2 expression. Data collected from our in vitro studies might have major implications for modifying the intestinal microbiota towards a healthier state in CD patients. Promoting the expression of HBD2 by colonic cells may lead to a lower rate of infection in these patients. Future in vivo studies are warranted to determine the potential clinical use of intra colonic administration of L-ILE in CD patients. The observed antimicrobial activity of HBD2 against bacterial isolates provides evidence that it is a crucial component of mucosal epithelial defense against infections which can complicate disease symptoms in CD.
Keywords: Crohn's disease; Host defense peptides; Human beta-defensins; Isoleucine; Antimicrobial activity; Minimal inhibitory concentration; Microbiology (0410); Molecular Biology (0307); Nutrition (0570)